Web Accessibility: A Foundation for Research - Yesilada, Yeliz; Harper, Simon (Human–Computer Interaction Series, 2019)
Covering key areas of evaluation and methodology, client-side applications, specialist and novel technologies, along with initial appraisals of disabilities, this important book provides comprehensive coverage of web accessibility. Written by leading experts in the field, it provides an overview of existing research and also looks at future developments, providing a much deeper insight than can be obtained through existing research libraries, aggregations, or search engines.